(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): In the paper we will research how to promote the values of social responsibility (SR) to affects the organization through the organizational culture. Purpose: The purpose of the article is to research the interdependence between organizational culture, values and SR of an organization with the objective to research the stimulation of implementation of the values of SR with the organizational culture. How this affects the development and operations of the organization will also be researched. Method: Research objectives will be achieved by using different methodologies. We will follow the MER Model of integral management and Dialectical Systems Theory, combined with the case study method. Based on theoretical issues and research results we will include our findings about how organizational culture can promote values of SR and their implementation in practice of the organization in discussion. Results: If the organizational culture is based on values of SR, can we by promoting of organizational culture achieve significant changes in the organization, which will be demonstrated in the case study of the Slovenian organization DOMEL Group. The summarized results of the theoretical principles of research and the case of the mentioned organization will be introduced. Organization: Improving the values of social responsibility influences positive on governance and management of the organization, thus governors and managers are more successful, and employees have greater well-being and are more successful. The success of the organization influences the success of the society. Society: By promoting the SR in the micro-environment of the organization one can also affect the macro environment in the industry and in the wider (social, natural) environment of organization because the organization affect to the various stakeholders. Organisations by promoting SR, promote accountability to their shareholders, employees and the (social, natural) environment. In addition to direct responsibility to capital such organizations are thus also SR and responsible towards the Planet Earth. Originality: The research has a significant influence on the development of research findings about the interdependence between organizational culture and values of SR and represents a holistic example of the development and business of an organization in which organizational culture and values have an important contribution to their efficiency, effectiveness, ethics and SR, and to the engaged employees who have good psychical well-being. Limitations / further research: The paper is limited by the research areas of organizational culture, values, SR and well-being of employees. The study will be limited on a case study of a representative organization. We will also make recommendations for practice and further research.